Measuring inequalities in health: the case for healthy life expectancy. Issue 12 (15th November 2006) - Wood, Rachael; Sutton, Matt; Clark, David; McKeon, Amy; Bain, Marion
Abstract : Objective: To evaluate healthy life expectancy (HLE) as a measure of health inequalities by comparing geographical and area-based deprivation-related inequalities in healthy and total life expectancy (TLE). Design: Life table analysis based on ecological cross-sectional data. Setting and population: Council area quarters and postcode sector-based deprivation fifths in Scotland. Main outcome measures: Expectation of life in good self-assessed general health, or free from limiting long-term illness, and TLE, for females and males at birth. Results: Women in Scotland have a life expectation of 70.3 years in good health, 61.6 years free from limiting long-term illness, and a TLE of 78.9 years. Comparable figures for men are 66.3, 58.6 and 73.5 years. TLE and HLE decrease with increasing area deprivation. Differences are substantially wider for HLE. A 4.7-year difference is seen in TLE between women living in the most and least deprived fifth of areas. The difference in HLE is 10.7 years in good health and 11.6 years free from limiting long-term illness. The degree of deprivation-related inequality in HLE is 2.5 times wider for women and 1.8 times wider for men than in TLE. Conclusions: Differences in TLE underestimate health inequalities substantially. By including morbidity and mortality, HLE reflects the excess burden of ill health experienced by disadvantaged populations better. Inequalities in length of life and health status during life should be taken into account while monitoring inequalities in population health.